Self-balancing feature of Lithium-Sulfur batteries - Knap, Vaclav; Stroe, Daniel-Ioan; Christensen, Andreas E.; Propp, Karsten; Fotouhi, Abbas; Auger, Daniel J.; Schaltz, Erik; Teodorescu, Remus (Elsevier, 2017)
The Li-S batteries are a prospective battery technology, which despite to its currently remaining drawbacks offers useable performance and interesting features. The polysulfide shuttle mechanism, a characteristic phenomenon for the Li-S batteries, causes a significant self-discharge at higher state-of-charge (SOC) levels, which leads to the energy dissipation of cells with higher charge. In an operation of series-connected Li-S cells, the shuttle mechanism results into a self-balancing effect which is studied here. A model for prediction of the self-balancing effect is proposed in this work and it is validated by experiments. Our results confirm the self-balancing feature of Li-S cells and illustrate their dependence on various conditions such as temperature, charging limits and idling time at high SOC.
Keywords: Inherent balancing; Lithium-Sulfur battery; Self-discharge; Series-connected batteries